Legal Framework for Resolving Election Violations in Indonesia: Towards Electoral Justice - Ali Umar Harahap; Achmad Busro; Ery Agus Priyono; Benny Sumardiana (Indonesian Journal of Criminal Law Studies, 2025)
Dealing with electoral violations in Indonesia faces persistent challenges, including strict time limits for case resolution, limited effectiveness of sanctions, and weak coordination among law enforcement agencies. Social and political dynamics further complicate evidence gathering, undermining the integrity of the electoral process. Electoral justice is therefore vital, both as a guarantee of legal certainty and a safeguard for voting rights, institutional integrity, and democratic legitimacy. This research applies a normative juridical method combined with qualitative analysis of statutory regulations, scholarly works, and legal records. The results indicate that the main obstacles to enforcement involve regulatory time constraints, ineffective sanctions, and institutional coordination gaps, compounded by socio-political factors. Nevertheless, electoral justice remains essential to uphold the rule of law and ensure free, fair, and genuine elections. Strengthening regulations, enhancing law enforcement capacity, and raising public legal awareness are necessary steps to secure credible elections and maintain democratic legitimacy.